Kajian Yuridis Tindak Pidana Pemalsuan Surat secara Bersama-Sama (Studi Kasus Putusan Pengadilan Negeri Jakarta Timur Nomor 305/Pid.B/2021/PN Jkt.Timur) - I Gede Eka Suantara; I Nyoman Gede Sugiartha; Ni Made Sukaryati Karma (Warmadewa Press, 2022)
Indonesia is a legal state in which all aspects are regulated by applicable law to determine the obligations, rights and obligations in monitoring one's own and social desires. Of course, the existence of applicable laws in Indonesia has a very good influence in order because it can control all kinds of criminal activities that occur in society. This study aims to reveal the form of criminal sanctions and legal considerations given by the panel of judges in imposing a sentence on the perpetrators of the crime of forging letters which were carried out together. This research uses normative legal writing method. Sources of data used are primary and secondary data. Data analysis is used in a qualitative, in-depth and comprehensive way and when analyzing legal materials, namely by argumentation through explaining legal incident materials or legal results in detail to facilitate interpretation in the analysis. The results in the study indicate that in terms of considering the judge's role when giving criminal sanctions to the defendant on behalf of Ahmad Saifudin in the decision Number 305/Pid.B/2021/PN Jkt.Tim, in which the defendant was sentenced for what he had done, he was sentenced to 1 year 2 months jail. The conclusion of the study is that joint criminal sanctions in carrying out the criminal act of forging letters together can be imposed as described in Article 263 paragraph (1) of the Criminal Code regarding the crime of forging letters, threatened with imprisonment for a maximum of six years. The researcher hopes that in deciding a case the judge can consider everything